2002
DOI: 10.1007/s00455-001-0098-0
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Consistency and Swallowing in Children and Adults

Abstract: Research has shown that swallowing in adults is affected by bolus consistency. Little is known, however, regarding the effect of bolus consistency on swallowing in children. Electromyographic (EMG) data from typically developing five- and eight-year-old-children and adults were obtained from the following muscles as they swallowed boluses of different consistencies: (1) right upper lip, (2) right lower lip, (3) submental, and (4) laryngeal strap. Signal analyses included calculating EMG onset and offset and av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 24 publications
2
43
0
3
Order By: Relevance
“…Reasons for referral included choking, coughing, gagging and/or vomiting during or after mealtime, gastroesophageal reflux, chest congestion, upper respiratory infections, or combinations of these concerns. VFSS Procedure Participants 7,8,9,11,12,13 and 15 were seated upright in a Multiple Application Multiple Articulation (MAMA) chair appropriate for infants, toddlers, and children up to 75 lb and 5 ft tall. The MAMA chair fits into standardized fluoroscopy units to allow for feeding and view of the swallow in the lateral projection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for referral included choking, coughing, gagging and/or vomiting during or after mealtime, gastroesophageal reflux, chest congestion, upper respiratory infections, or combinations of these concerns. VFSS Procedure Participants 7,8,9,11,12,13 and 15 were seated upright in a Multiple Application Multiple Articulation (MAMA) chair appropriate for infants, toddlers, and children up to 75 lb and 5 ft tall. The MAMA chair fits into standardized fluoroscopy units to allow for feeding and view of the swallow in the lateral projection.…”
Section: Methodsmentioning
confidence: 99%
“…Group II included six children with mean age of 10.80 ± 2.16 months. Ruark et al [11] found that by 5 years of age children have similar swallowing strategies for managing bolus consistency compared to adults. The four children in Group III had deciduous teeth and mean age of 36.00 ± 10.95 months.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…From 10147 search results, 488 articles described a measurement of swallowing using more than one consistency of food or liquid but only 36 met quality criteria and relevance. Thicker liquids were reported to increase the duration of swallowing events in accelerometry [29], electromagnetic articulography [30], ultrasound [31] and surface electromyography signals [32], [33], [34], and also on videofluoroscopy for pharyngeal transit time measures [35], [36], although more recently a study found no effect of thickening on bolus velocity [37]. Regarding dysphagia, several videofluoroscopic studies provided evidence of texture modification having a measurable effect on swallowing efficacy [38], [39], [40], [41], e.g.…”
Section: Clinical Evidence Relating To Texture Modification and Swallmentioning
confidence: 99%
“…It has been established that children use a similar swallowing method to adults from the age of five, and it has also been suggested that children under six years old find it harder to swallow tablets and capsules 12, 13. Despite this, it has been shown that preschool children can swallow tablets at the age of three, with training 14, and our study also found that preschool children could often swallow tablets and capsules before the use of the in situ coating.…”
Section: Discussionmentioning
confidence: 99%